Global seamless network demonstrator a comprehensive ASON - Foisel, Hans-Martin.
This article reports on the continuous activities of Deutsche Telekom in setting up comprehensive ASON/GMPLS network demonstrators. The goal is to enable practical evaluations and early experiences with prototype implementations related to new standards and specifications from ITU-T, IETF, and OIF. Evolving from the GSN Demonstrator toward the current GSN+ Demonstrator configuration, this field testbed comprises ASON/GMPLS-based backbone network domains, as well as key client networks such as IP, Ethernet (metro and access networks), storage area networks, and broadband video applications to exemplify the wide range of network functions enabled by these new technologies. These ASON/GMPLS demonstrator activities were embedded in the OIF World Interoperability Tests and Demonstration in 2004, and are linked with the German national (VIOLA) and pan-European (MUPBED) project activities ensuring the highest level of interoperable implementations.
Keywords: GMPLS; automatically switched optical networks; global seamless network demonstrator; interoperability test